2023
DOI: 10.1177/20420188231197921
|View full text |Cite
|
Sign up to set email alerts
|

Association of hyponatremia with bone mineral density and fractures: a narrative review

Ploutarchos Tzoulis,
Maria P. Yavropoulou

Abstract: Recent studies suggest a possible association of hyponatremia with osteoporosis, falls and bone fractures. The objectives of this narrative review were to further explore this association and the related pathophysiological mechanisms and to suggest a practical approach to patients with osteoporosis or chronic hyponatremia in clinical practice. We conducted an extensive PubMed search until October 2022 with the combination of the following keywords: ‘hyponatremia’ or ‘sodium’ or ‘SIADH’ and ‘fractures’ or ‘bone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 62 publications
(188 reference statements)
0
2
0
Order By: Relevance
“…Second, the usage of drugs and nutritional state in this study population are unclear, which may contribute to bias in the interpretation of the data. Third, some diseases, such as hypophosphatemia or metabolic alkalosis [47], syndrome of inappropriate antidiuretic hormone secretion (SIADH) [11,25], primary hyperaldosteronism [48,49], Cushing syndrome [50][51][52], and Bartter syndrome [53], may be strongly linked to hyponatremia or hypokalemia and fracture incidence but were not excluded or analyzed in this study. Finally, the study is confined to a single trauma center, potentially limiting the generalizability of its findings to broader populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, the usage of drugs and nutritional state in this study population are unclear, which may contribute to bias in the interpretation of the data. Third, some diseases, such as hypophosphatemia or metabolic alkalosis [47], syndrome of inappropriate antidiuretic hormone secretion (SIADH) [11,25], primary hyperaldosteronism [48,49], Cushing syndrome [50][51][52], and Bartter syndrome [53], may be strongly linked to hyponatremia or hypokalemia and fracture incidence but were not excluded or analyzed in this study. Finally, the study is confined to a single trauma center, potentially limiting the generalizability of its findings to broader populations.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, certain authors have suggested that hyponatremia and hypokalemia should be regarded as indicators of compromised health rather than as isolated risk factors for fractures [20]. Furthermore, although hip fractures are consistently identified as the most prevalent among patients with hyponatremia [4,[22][23][24][25], no distinct order is established regarding the ranking of other fracture sites. Furthermore, there are also no published reports concerning the location of fractures associated with hypokalemia.…”
Section: Introductionmentioning
confidence: 99%